Bosnia and Herzegovina : Request for Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Bosnia and Herzegovina. (IMF Staff Country Reports; Country Report ;, 2020)
This paper presents Bosnia and Herzegovina's Request for Purchase Under the Rapid Financing Instrument (RFI). RFI is expected to help provide support for scaling up priority spending on health and social assistance, while preserving debt sustainability. Preserving the currency board arrangement and raising the resilience of the banking system play a crucial role for restoring external and internal balances. High frequency monitoring of the banks, including their liquidity positions and asset quality, is crucial at this juncture. Economic activity is tentatively projected to decline by 5 percent in 2020 on account of a pronounced fall in exports and remittances and reduced domestic demand and supply. High political uncertainties pose additional downside risks. Despite a recent easing of political tensions, the complexity of the political environment is a downside risk, which could lead to policy slippage and weakened response measures. The IMF staff supports the authorities' request for a purchase under the RFI considering the urgent nature of the external financing needs caused by the coronavirus disease 2019 crisis.